2016
DOI: 10.29252/jrdms.1.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Accuracy of Cone Beam Computed Tomography,Digital Intraoral Radiography and Conventional Intraoral Radiography in the Measurement of Periodontal Bone Defects

Abstract: ARTICLE INFOBackground and Aim: Cone beam computed tomography (CBCT) produces highquality data in periodontal diagnosis and treatment planning. The aim of this study was to compare the accuracy of CBCT with intraoral digital and conventional radiography in the measurement of periodontal bone defects. Methods and Materials: In this diagnostic research, two hundred and eighteen artificial osseous defects (buccal and lingual infra-bony, inter proximal, horizontal, crater, dehiscence and fenestration defects) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This difficulty in diagnosis leads to unnecessary tooth extractions, poor long-term prognosis and extensive bone loss. (2)(3)(4) In this in vitro study, the diagnostic accuracy of digital intraoral radiography with PSP and CBCT in the detection of HRF and VRF was assessed.…”
Section: -Diagnostic Results Of the Two Observers Regarding Hrf And Vmentioning
confidence: 99%
“…This difficulty in diagnosis leads to unnecessary tooth extractions, poor long-term prognosis and extensive bone loss. (2)(3)(4) In this in vitro study, the diagnostic accuracy of digital intraoral radiography with PSP and CBCT in the detection of HRF and VRF was assessed.…”
Section: -Diagnostic Results Of the Two Observers Regarding Hrf And Vmentioning
confidence: 99%
“…CBCT is a suitable modality for evaluation of buccal and lingual cortical plates and better visualization of the morphology of bone defects [ 14 - 16 ]. Bagis et al, [ 10 ] and Dehghani et al, [ 17 ] compared the diagnostic accuracy of CBCT with periapical radiography for detection of tunnel, fenestration and dehiscence bone defects and showed higher diagnostic accuracy of CBCT than periapical radiography. Also, they demonstrated that the diagnostic accuracy of CBCT increased with an increase in size of defects, which was in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] and Dehghani et al . [ 15 ] compared the diagnostic accuracy of CBCT with PA radiography for detection of tunnel, fenestration, and dehiscence bone defects and showed higher diagnostic accuracy of CBCT than PA radiography.…”
Section: Discussionmentioning
confidence: 99%